Answer:
![\frac{2(c+2)}{c(c-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%28c%2B2%29%7D%7Bc%28c-2%29%7D)
Step-by-step explanation:
![\frac{c^{2}-4 }{6c^{4}+15c^{3}}=\frac{(c-2)(c+2)}{c(6c^{3}+15c^{2}) }](https://tex.z-dn.net/?f=%5Cfrac%7Bc%5E%7B2%7D-4%20%7D%7B6c%5E%7B4%7D%2B15c%5E%7B3%7D%7D%3D%5Cfrac%7B%28c-2%29%28c%2B2%29%7D%7Bc%286c%5E%7B3%7D%2B15c%5E%7B2%7D%29%20%7D)
Identity used:
![a^{2}-b^{2}=(a-b)(a+b)](https://tex.z-dn.net/?f=a%5E%7B2%7D-b%5E%7B2%7D%3D%28a-b%29%28a%2Bb%29)
![\frac{c^{2}-4c+4}{12c^{3}+30c^{2}}=\frac{(c-2)^{2}}{2(6c^{3}+15c^{2}) }](https://tex.z-dn.net/?f=%5Cfrac%7Bc%5E%7B2%7D-4c%2B4%7D%7B12c%5E%7B3%7D%2B30c%5E%7B2%7D%7D%3D%5Cfrac%7B%28c-2%29%5E%7B2%7D%7D%7B2%286c%5E%7B3%7D%2B15c%5E%7B2%7D%29%20%7D)
Now let us divide the modified expressions:
÷ ![\frac{(c-2)^2}{2(6c^{3}+15c^{2}) }](https://tex.z-dn.net/?f=%5Cfrac%7B%28c-2%29%5E2%7D%7B2%286c%5E%7B3%7D%2B15c%5E%7B2%7D%29%20%7D)
we get:
![\frac{2(c+2)}{c(c-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%28c%2B2%29%7D%7Bc%28c-2%29%7D)
Answer:
( 2 - x )^2
Step-by-step explanation:
Part a: subtract 48-30=18
Part b: i found it by subtracting 48 -30 because it says left over
12.5 kilometers per liter
Answer:
b. 4x^2 -7x +5
Step-by-step explanation:
When you know a sum and one of its contributors, you can find the other by subtraction. The other trinomial is ...
(7x^2 -5x +4) - (3x^2 +2x -1)
= (7 -3)x^2 +(-5 -2)x +(4 -(-1))
= 4x^2 -7x +5 . . . . . matches B